Some Approximation Properties in Musielak-Orlicz-Sobolev Spaces: A. Benkirane, M. Ould Mohamedhen Val - Team, Support (Thai Journal of Mathematics, 2012)
Some approximation theorems involving the modular convergence, which improve known density results of interest in the existence theory for strongly nonlinear boundary value problems are presented.